Study on removal of oxide from carrier salt in molten salt reactor by vacuum distillation - ZHENG Xiaoqiang; DOU Qiang; CHENG Ming; LI Qingnuan; FU Haiying; LI Wenxin; YAN Liuming (He jishu, 2022)
BackgroundIn molten salt reactor, the concentration of oxygen impurities in the molten salt should be strictly controlled to avoid the potential safety risks caused by the reaction of O2- in the carrier salt with UF4 fuel to generated UO2 precipitation.PurposeThis study aims to investigate the evaporation behavior of the main oxygen-containing impuritiy ions in carrier salt at high temperature and low pressure and the influence of process parameters such as temperature, pressure and initial oxygen content of molten salt on the removal of O2- in carrier salt.MethodsThe vacuum distillation method was employed and a vacuum distillation device were used to carried out experimental study of the separation behavior of the main oxygen-containing impurities NO3-, SO42-, PO43- and O2- in the carrier salt during vacuum distillation. The removal mechanism of the above ions was explored, and the specific influence of process conditions on the separation effect of O2- distillation was investigated.ResultsThe results show that the removal ability of oxygen-containing impurities by vacuum distillation is NO3-＞PO43-＞SO42-＞O2-. The removal capacity of O2- increases with the increase of temperature, and the recovered salt with a total oxygen content about 2.40×10-4 g·g-1 salt is obtained at 1 050 ℃. The phenomenon of oxygen with a total oxygen content about 2.50×10-4 g·g-1 salt is observed when the pressure is higher than 40 Pa. The oxygen entrainment is increased during the evaporation of molten salt with the decrease of pressure, and the recovered salt content in the recovered salt continued to decrease with the decrease of the initial content of O2- in the carrier salt, which confirmed the technical feasibility of melting salt multiple distillation to remove oxygen.ConclusionsIt is verified by study shows that vacuum distillation can remove oxygen-containing impurities from carrier salt effectively and achieve the rapid and efficient purification of the carrier salt.